Kitap İncelemesi: THE EUROPEAN UNION’S NEW FOREIGN POLICY - Emre Erdemir (Ankara Avrupa Çalışmaları Dergisi)
Today, the European Union (EU) is trying to determine its place in the international system where there are multipolar power centers. Editor Martin Westlake and other contributing authors lay out the foundations of the Union's new foreign policy in “The European Union's New Foreign Policy.” The foreign policy issue, which has been under the jurisdiction of the Member States for many years, has become a phenomenon with the Common Foreign and Security Policy column created with the Maastricht Treaty signed in 1992 (p.1). This phenomenon also raises the book's fundamental research question: Why is there a need to explain the "old" foreign policy as "new" today? The book, which was synthesized from different perspectives by more than one author, makes sense of the new foreign policy of the EU with its constitutional, institutional, political and geographical aspects. The presence of the word “new” reflects the tools, actors, initiatives, and the EU framing these factors (p.2).